2022
DOI: 10.3791/63905
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic <em>Ex Vivo</em> Pancreas Perfusion for the Preservation of Pancreas Allografts before Transplantation

Abstract: Pancreas transplantation (PTx) is a curative treatment for people who live with the burden of a diagnosis of diabetes mellitus (DM). However, due to organ shortages and increasing numbers of patients being listed for PTx, new strategies are needed to increase the number of available grafts for transplantation.Static cold storage (SCS) is considered the gold standard for standard criteria organs.However, standard criteria donors (SCD) are becoming scarce and new strategies that can increase the rate of organ ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…16 Similarly, for dialysate, we used a higher concentration of salt (1.5 versus 1 g/L as previously described) based on lower edema and more physiological perfusion milieu achieved by us in a series of our previous perfusion experiments. 15 At the back-table, all arterial branches were tied off, and the spleen was removed. Next, the aorta was cannulated using a 1/4" × 3/8" cannula (in the NEVP group).…”
Section: Protocol For Nevpmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Similarly, for dialysate, we used a higher concentration of salt (1.5 versus 1 g/L as previously described) based on lower edema and more physiological perfusion milieu achieved by us in a series of our previous perfusion experiments. 15 At the back-table, all arterial branches were tied off, and the spleen was removed. Next, the aorta was cannulated using a 1/4" × 3/8" cannula (in the NEVP group).…”
Section: Protocol For Nevpmentioning
confidence: 99%
“…The anesthetic and surgical procedures in the donor operation were performed according to the step-by-step protocol described in detail previously by our group. 15 A policy of minimal handling of the native pancreas was followed to ensure a minimally inflamed graft at the end of the operation. After systemic administration of heparin (500 IU/kg bodyweight) through the central venous catheter, blood was drained and collected (usually 800-1000 mL) in bags containing Citrate Phosphate Dextrose Saline Adenine Glucose-Mannitol (CPD/ SAG-M), used later as a component in the perfusate used in NEVP.…”
Section: Surgery and Anesthesia Protocol (Donor Operation)mentioning
confidence: 99%
“…Animal studies further supported the recent findings with perfusion of human pancreases. Shorter endischemic NMP of 90min to 5hrs resulted in well-maintained tissue and limited inflammation [8,30,31,[49][50][51][52][53][54]. Most studies included DBD pancreas and lack a high risk donor model.…”
Section: Normothermic Pancreas Perfusionmentioning
confidence: 99%
“…In-house devices and ECMO-based equipment were used by many. Various perfusate compositions were reported in the literature with autologous whole blood or washed erythrocytes as oxygen carriers in most recent studies [30,31,49]. Particularly in older studies the cold ischemia time before NMP is frequently not reported (Supplementary Table 2) [8,[52][53][54][55].…”
Section: Normothermic Pancreas Perfusionmentioning
confidence: 99%
See 1 more Smart Citation